Impact of Tax Rates and Sales Growth On Tax Avoidance - Suaidah, Imarotus; Rahayu, Puji (Innovation Business Management and Accounting Journal, 2023)
This research aims to examine the effect of tax rates and sales growth on tax avoidance. This research is focused on telecommunications companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2022 period. The sampling technique uses the purposive sampling method which amounts to 42 samples. As for the data analysis technique used is multiple regression analysis by testing classical assumptions first. The results of the data analysis that have been carried out show that the tax rate does not affect tax avoidance in telecommunications companies, while sales growth has an influence on tax avoidance of 0.389 which is included in the low category, then the tax rate and sales growth have an influence together on tax avoidance by 13.5%.